The Role of Islamic Social Finance in Covid-19 - Putra, Trisno Wardy; Trimulato, Trimulato; Muhlis, Muhlis; Fajrin, Farid; Supriadi, Supriadi (Jurnal Iqtisaduna, 2020)
The focus of this research is to discuss the role of Islamic social finance especially zakat, infaq, alms and endowments in the face of the covid-19 pandemic. This study uses qualitative and descriptive methods with techniques for studying literature (library research). The results showed that Islamic social finance can be a solution in handling Covid-19, by using zakat funds, donations and alms in meeting consumptive needs and endowment funds used in health infrastructure assistance.